Pengaruh Persepsi Siswa atas Lingkungan Belajar dan Penguasaan Kosa Kata Terhadap Kemampuan Berbicara Bahasa Inggris Siswa Sekolah Menengah Atas Swasta Balaraja - Eva Agistiawati; Masduki Asbari (Universitas Muhammadiyah Enrekang, 2020)
This study aims to determine the effect of students' perceptions on the learning environment and vocabulary mastery of English speaking ability at Balaraja Private High School. The method used in this study is a survey with correlation and regression analysis, which is connecting data that shows the level of students' perceptions of the learning environment and vocabulary mastery with the ability to speak English in Balaraja Private High Schools. Sampling is done by random sampling technique. Total population of 806 with respondents in this study was 60 students. The research instruments used were questionnaires and multiple choice test questions. The results showed that: 1) there was a significant influence on students' perceptions of the learning environment and shared vocabulary mastery of the ability to speak English in private high school students in Kec. Balaraja, Banten. This is evidenced by the acquisition of Sig. 0,000 <0.05 and Fh = 14,160. Together, the perception of the learning environment and vocabulary mastery contributed 33.2% to the variable in English speaking ability. 2) There is a significant influence of perceptions on the learning environment on the ability to speak English in high school students in Kec. Balaraja, Banten. This is evidenced by the acquisition of Sig. 0.013 <0.05 and th = 2.578. Perception variable on learning environment contributed 14.32% in improving English speaking ability. 3) There was a significant influence on vocabulary mastery on English speaking ability of private high school students in Kec. Balaraja, Banten. This is evidenced by the acquisition of Sig. 0.003 <0.05 and th = 3.144. The vocabulary mastery variable contributed 18.90% in improving the ability to speak English.